2003
DOI: 10.1196/annals.1301.021
|View full text |Cite
|
Sign up to set email alerts
|

Nonhuman Primate Models to Study Anxiety, Emotion Regulation, and Psychopathology

Abstract: This paper demonstrates that the rhesus monkey provides an excellent model to study mechanisms underlying human anxiety and fear and emotion regulation. In previous studies with rhesus monkeys, stable, brain, endocrine, and behavioral characteristics related to individual differences in anxiety were found. It was suggested that, when extreme, these features characterize an anxious endophenotype and that these findings in the monkey are particularly relevant to understanding adaptive and maladaptive anxiety res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
158
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 81 publications
5
158
0
Order By: Relevance
“…As mentioned above, behavioral inhibition is characterized by a tendency to withdraw and inhibit behavior in response to novel stimuli (Fox et al, 2005). Rhesus monkeys with behavioral inhibition have elevated concentrations of CRH in cerebrospinal fluid and increases in plasma cortisol (Kalin and Shelton, 2003). Similarly, social wariness and internalizing behaviors in children are positively associated with basal salivary cortisol concentrations (de Haan et al, 1998;Gunnar et al, 1997;Kagan et al, 1987;Scerbo and Kolko, 1994;Schmidt et al, 1997;Smider et al, 2002), and two studies have found an association between behavioral inhibition and genetic markers at the CRH locus (Smoller et al, 2003(Smoller et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, behavioral inhibition is characterized by a tendency to withdraw and inhibit behavior in response to novel stimuli (Fox et al, 2005). Rhesus monkeys with behavioral inhibition have elevated concentrations of CRH in cerebrospinal fluid and increases in plasma cortisol (Kalin and Shelton, 2003). Similarly, social wariness and internalizing behaviors in children are positively associated with basal salivary cortisol concentrations (de Haan et al, 1998;Gunnar et al, 1997;Kagan et al, 1987;Scerbo and Kolko, 1994;Schmidt et al, 1997;Smider et al, 2002), and two studies have found an association between behavioral inhibition and genetic markers at the CRH locus (Smoller et al, 2003(Smoller et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral inhibition is another temperament factor that has been found predictive of anxiety disorders and depression (Fox et al, 2005). This trait, defined as the tendency to withdraw and avoid novel situations, demonstrates stability over time in both non-human primates (Kalin and Shelton, 2003) and children (Fox et al, 2005). Behavioral inhibition has been linked to anxiety disorders in family studies and in prospective longitudinal studies of young children who have been followed through childhood (Hirshfeld et al, 1992;Rosenbaum et al, 1988) and into adolescence (Prior et al, 2000;Schwartz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the impacts of different types of ethologically relevant stressors on behavioral, neurochemical, physiological and brain functional responses have been well characterized in this species. [26][27][28] We have been performing highresolution FDG microPET scans in rhesus monkeys to explore the relation between patterns of brain metabolic activity and individual differences in anxiety-related traits. For example, we previously demonstrated that when threatened by a human intruder for a 30-min period, monkeys' individual differences in metabolic activity in the bed nucleus of the stria terminalis (BNST) are strongly predictive of individual differences in monkeys' anxiety-related freezing responses.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have optimized a model of anxious temperament (AT), the conserved at-risk phenotype, in young developing rhesus monkeys (1)(2)(3)(4). The rhesus monkey is ideal for studying the origin of human AT because these species share the genetic, neural, and phenotypic underpinnings of complex social and emotional functioning (5)(6)(7)(8)(9)(10). Importantly, the rhesus developmental model bridges the critical gap between human psychopathology and rodent models, allowing for translation to humans by using in vivo imaging measures and translation to rodents by using ex vivo molecular methods.…”
mentioning
confidence: 99%